2021
DOI: 10.4081/reumatismo.2020.1325
|View full text |Cite
|
Sign up to set email alerts
|

Top 100 cited articles on ankylosing spondylitis

Abstract: Ankylosing spondylitis is a global health problem. There are continuous innovations in terms of etiopathogenesis, diagnosis, and treatment. Here, the top 100 most cited articles on ankylosing spondylitis during the last three decades are analyzed. On April 6, 2020, the Web of Science was screened from 1984 to 2020 using the terms ankylosing spondylitis; the top 100 most cited articles were identified. For bibliometric analysis, the name of the article, year of publication, author information, number of citatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In the study conducted by Yin et al (13), when the study types were examined, it was reported that the reviews came after the randomized controlled, prospective clinical study types. Similarly, in the study of Bagcier et al (17), randomized controlled, prospective clinical study types are in the first place. Similar to the literature, randomized controlled, prospective clinical study is in the first place in our study, followed by reviews.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the study conducted by Yin et al (13), when the study types were examined, it was reported that the reviews came after the randomized controlled, prospective clinical study types. Similarly, in the study of Bagcier et al (17), randomized controlled, prospective clinical study types are in the first place. Similar to the literature, randomized controlled, prospective clinical study is in the first place in our study, followed by reviews.…”
Section: Discussionmentioning
confidence: 99%
“…In the bibliometric study of Akyol et al (16), including publications on rehabilitation in Ankylosing Spondylitis, the authors were mostly from Germany, followed by Turkey and the USA, Bagcier et al (17) In his study of the most cited articles in ankylosing spondylitis, it was determined that the authors were mostly nationals of Germany, the Netherlands and then the United Kingdom, respectively. Turkey, Japan, and then the United Kingdom were the countries that contributed the most to the BD-related studies in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations